Synthesis, Characterization, and Reactivity of a Uranium(VI) Carbene Imido Oxo Complex1. Issue 26 (19th May 2014) - Lu, Erli; Cooper, Oliver J.; McMaster, Jonathan; Tuna, Floriana; McInnes, Eric J. L.; Lewis, William; Blake, Alexander J.; Liddle, Stephen T.
Abstract We report the uranium(VI) carbene imido oxo complex [U(BIPMTMS)(NMes)(O)(DMAP)2] (5, BIPMTMS=C(PPh2NSiMe3)2; Mes=2, 4, 6‐Me3C6H2; DMAP=4‐(dimethylamino)pyridine) which exhibits the unprecedented arrangement of three formal multiply bonded ligands to one metal center where the coordinated heteroatoms derive from different element groups. This complex was prepared by incorporation of carbene, imido, and then oxo groups at the uranium center by salt elimination, protonolysis, and two‐electron oxidation, respectively. The oxo and imido groups adopt axial positions in a T‐shaped motif with respect to the carbene, which is consistent with an inverse trans‐influence. Complex 5 reacts with tert‐butylisocyanate at the imido rather than carbene group to afford the uranyl(VI) carbene complex [U(BIPMTMS)(O)2(DMAP)2] (6).